Comparing ovarian reserve parameters after laparoscopic endometrioma resection in the follicular vs. luteal phase: a prospective cohort study - Takmaz, Ozguc; Asoglu, Mehmet Resit; Ceyhan, Mehmet; Unsal, Gozde; Gungor, Mete (Frontiers in Medicine, 2024)
Objective To evaluate whether performing laparoscopic endometrioma surgery in the follicular or luteal phase affects changes in ovarian reserve. Methods This prospective cohort study was conducted in a university-affiliated hospital. A total of 55 women who underwent unilateral laparoscopic endometrioma removal were included in the study. Of these, 28 were in the follicular phase of the menstrual cycle (follicular group), and 27 were in the luteal phase (luteal group). The primary outcomes were the rates of decreased anti-Mullerian hormone (AMH) levels and antral follicle counts (AFC) 6 months after the surgery, which were compared between the groups. Results The groups were similar in patient characteristics and endometrioma sizes. AMH levels and AFCs were significantly lower in the post-operative 6th month compared with their pre-operative values (p < 0.05 for both groups). The rate of decrease in AMH levels 6 months after the surgery was not significantly different between the follicular and luteal groups (24.5 and 19.5%, respectively, p > 0.05). Similarly, the rate of decrease in AFCs 6 months after the surgery did not differ between the groups (13.4 and 14.3%, respectively, p > 0.05). Conclusion Performing laparoscopic endometrioma surgery, whether in the follicular or luteal phase, does not seem to affect the changes in the ovarian reserve. Clinical trial registration https://clinicaltrials.gov/study/NCT03484546, identifier NCT034845.